Effectiveness of acupuncture combined mecobalamin in the treatment of elderly diabetic peripheral neuropathy: A protocol of systematic review and meta-analysis - Duan, Yu-hong (Medicine (Baltimore), 2020)
BACKGROUND: Although previous studies have reported the effectiveness of acupuncture combined mecobalamin (AM) in the treatment of elderly diabetic peripheral neuropathy (EDPN), no systematic study has assessed its effectiveness and safety. Thus, this study will evaluate the effectiveness and safety of AM for the treatment of patients with EDPN. METHODS: Bibliographic electronic databases will be searched as follows: Cochrane Library, PUBMED, EMBASE, CINAHL, PsycINFO, WANGFANG, and China National Knowledge Infrastructure. All of them will be searched from each database initial to March 1, 2020 without language restrictions. All study selection, information extracted, and study quality evaluation will be performed by 2 independent authors. Any disagreements between 2 authors will be resolved by a third author via discussion. RevMan 5.3 software will be used for data pooling and meta-analysis performance if it is possible. RESULTS: This study will provide synthesis of current evidence of AM for patients with EDPN through primary outcome of glycemic profile, and secondary of neuropathic pain intensity, plantar tactile sensitivity, sensory nerve conduction velocity and motor nerve conduction velocity, health-related quality of life, and adverse events. CONCLUSION: This study will provide helpful reference for the efficacy and safety of AM for the treatment of patients with EDPN to the clinicians and further studies. Study registration number: INPLASY202040094.